The effective manager - Horstman, Mark; Sentes, Sarah; Braun, Kate (Business consultant) (Wiley, 2023)
"An effective manager is one who achieves results and retention. Can you get the job done -- whether it be sales, or engineering, or marketing, or operations, or logistics, or software development? And can you do so in a way that not just attracts but also retains your team of professionals? Will you keep your people while you climb the mountain, or will you burn them out in hopes of getting promoted and being able to do the same thing to a different team? The Effective Manager is the only management book to describe specific, actionable steps to achieve the 4 critical manager behaviors (Know Your People; Talk About Performance; Ask For More; Push Work Down). Most management books are written for CEOs, to encourage a change in corporate management. The Effective Manager is written for every manager, at every level. It focuses on what you can do now, today, with your team members, to improve their performance and get better results and retention. And this second edition will feature updates to some of the existing content and will also feature new chapters that cover topics like: how to deal with the challenges of remote work; how to maintain an effective culture in a WFH or hybrid office culture; how to lead with empathy and compassion, and much more"--